G17(P) Transition to adult care audit: successes and challenges at a tertiary children's hospital. (12th March 2018) - Low, A; Culshaw, J; Narula, P
Abstract : Background: The period of transition from paediatric to adult care is a risky one. Recent NICE guidelines and the national Ready, Steady, Go (RSG) initiative aim to improve the transition process for young people (YP). We present an overview and audit of current transition services at a tertiary paediatric hospital where a 2016 Care Quality Commission inspection labelled Transition Services as 'Requires improvement.' In response, the hospital has appointed two transition nurses, encouraged the implementation of RSG and set up a transition website for YP to access. Methods: We reviewed two weeks of inpatient data to find patients with medical conditions requiring transition, and compared their care to the NICE recommendations: Did discussions around transition begin by age 14 (or at diagnosis)? Was there an annual meeting where transition was discussed? Was there evidence of a named transition worker? Did they meet a practitioner from adult services before transferring? Results: 43 patients were included in our audit, with the oldest being 20 years old. 58% had started transition, but only 36% by the age of 14.30% had an annual review, and 20% had a named worker. 48% had met someone from adult services before transition. Of patients with complex problems under three or more specialties, 66% had transition started but none by the age of 14. Medical specialties fared better than surgical specialties across all domains. Conclusion: This is the first time this audit has been conducted at this hospital. Our audit demonstrates that despite the recent improvements in transition services, our hospital still faces challenges in meeting the NICE transition guidelines. The patients least likely to meet the guidelines were surgical patients and complex patients under the care of multiple specialties. Further plans include mandatory training on transition, and consideration of YP using a tablet to access RSG in the waiting room before appointments.